HPLC Determination of α-Oxoaldehydes and α-Oxoacids from Human Serum of Diabeties and Uremic Patients Using 4-Nitro-1,2-phenylenediamine as Derivetizing Reagent - Mahar, K.P.; Khuhawar, M.Y.; Mastoi, G.M.; Kazi, T.G.; Abbasi, K.; Channar, A.H. (Asian Journal of Chemistry, 2011)
Reversed phase HPLC method has been developed for the determination of α-oxoaldehydes: glyoxal (Go) and methylglyoxal (MGo) and α-oxoacids: 3-methyl-2-oxovaleric acid (K3MVA), 2-oxoglutaric acid (KG), 4-methyl-2-oxovaleric acid (K4MVA) and phenylpyruvic acid (PPY) using 4-nitro-1,2-phenylenediamine (NPD) as derivatizing reagent. HPLC was carried out on a Zorbax C-18 column with isocratic elution using methanol-water-acetonitrile (46:52:2 v/v/v) as mobile phase at a flow rate of 0.9 mL/min. UV detection was carried out by photodiode array at 255 nm. Calibration curves were linear in the rage of 0.2-100 μg/mL and limit of detections were from 0.045-2.5 μg/mL. The method was applied for the determination of α-oxoaldehydes and α-oxo acids from the serum of diabetic and uremic patients. The results obtained were compared with healthy volunteers. Higher concentration of oxoaldehydes and oxoacids were observed in the uremic patients. The result obtained indicated relative standard deviation (RSD) within 1.1-2.2 %.